Startle epilepsy triggered by a light bump: a rare case confirmed with ambulatory electroencephelography - Sachin,; Khan, Sharukh; Suri, Madhav; Arshad, Mohammad S.; Verma, Archana (International Journal of Research in Medical Sciences, 2025)
Reflex epilepsy is characterized by seizures triggered by specific sensory or cognitive stimuli, with startle-induced epilepsy being a rare subtype often misdiagnosed due to non-specific findings on routine electroencephalography (EEG). We report the case of a 16-year-old boy with a history of hypoxic-ischemic encephalopathy who experienced frequent episodes of sudden muscle stiffness, myoclonic jerks, tonic posturing of limbs, and occasional loss of consciousness, consistently triggered by sudden tactile or auditory stimuli such as a light bump. The seizures began at age 11 and fluctuated in frequency, occurring up to 8–9 times per day. Previous magnetic resonance imaging (MRI) revealed bilateral temporal gliosis and frontal encephalomalacia, but routine EEGs at ages 12 and 15 were normal, leading to diagnostic uncertainty and ineffective treatment with several anti-seizure medications. A 24-hour ambulatory EEG successfully captured an ictal event triggered by a slight bump, revealing high-amplitude sharp and wave discharges over the bilateral temporal regions with frontal extension. Interictal epileptiform discharges and epileptic K-complexes were also noted. With the confirmation of startle epilepsy, the patient was started on appropriate antiepileptic treatment and advised behavioral modifications, resulting in a reduction of seizure frequency to 4–5 episodes per week. This case underscores the clinical value of prolonged EEG monitoring in cases of suspected reflex epilepsy, particularly when routine evaluations are inconclusive. Ambulatory EEG plays a crucial role in diagnosing rare seizure types and enabling timely, targeted therapy that can improve patient outcomes.